A Multidisciplinary Evaluation of Barriers to Enrolling Cancer Patients into Early Phase Clinical Trials: Challenges and Patient-centric Recommendations. (3rd August 2019) - Babiker, Hani M; Davis, Lisa; Larson, Kristian; Placencia, Crystal; Swensen, Connor; Tenneti, Pavan; Lim, Melissa; Cañamar, Ruth; Curtis, Jacqueline; Castillo, Erica; Mancuso, James; Rensvold, Diane; et al.
ABSTRACT: Introduction : Early phase clinical trials are the first clinical research step to bringing new cancer therapeutics to patients. At this stage, a new drug's safety, dosing, and scheduling profiles are established as the main endpoints. However, excellent responses due to biomarker-guided and immune checkpoint trials in early phase have resulted in direct approvals of new anti-cancer drugs. Despite doubling of the success rate of new drug approvals, many barriers exist to expeditiously bring active new drugs to the clinic. Areas covered : This review covers roles of members of the early phase program and the challenges they face in enrolling advanced cancer patients to trials. Practical solutions are provided from the perspective of the investigators, regulatory, investigational pharmacy, research nurses, clinical research coordinators, budgets, contracts, and data management. Expert opinion : We are witnessing a burgeoning era in drug development with rapid approval of efficacious drugs. This is achieved by a strong collaboration between investigators, academic institutions, pharmaceutical sponsors, scientists, Food and Drug Administration (FDA), and community practices. Herein, we discuss some of the challenges faced by early phase clinical trials programs and discuss methods of improvement.